Creating Actionable Insights Using Tableau CRM - Tossell, Mark (Packt Publishing, 2021)
Leverage Tableau CRM to generate valuable business insights and solve business problems efficiently Key Features Extract, combine, transform, and visualize your data to derive business insights using Tableau CRM Gain hands-on experience as you walk through practical dashboard use cases in Tableau CRM Learn how to build best-in-class dashboards from a Tableau CRM thought leader Book Description Tableau CRM, formerly Einstein Analytics, is a powerful and versatile data analytics platform that enables organizations to extract, combine, transform, and visualize their data to create valuable business insights. Despite being a highly capable tool and in high demand in the industry, proficiency in Tableau CRM skills is hard to find. Creating Actionable Insights Using Tableau CRM provides a hands-on approach to Tableau CRM implementation and associated methodologies that will have you up and running and productive in no time. The book provides you with detailed explanations of essential concepts to help you to gain confidence and become competent in using the Tableau CRM platform for data extraction, combination, transformation, visualization, and action. As you make progress, you'll understand what Tableau CRM is and where it provides business value. You'll also learn how to bring your data together in Tableau CRM, build datasets and lenses for data analysis, create effective analytics dashboards for visualization and consumption by end users, and build dashboard actions that take the user from data to insight to action with ease. By the end of this Tableau book, you'll be able to solve business problems using Tableau CRM and design, build, test, and deploy Tableau CRM analytics dashboards efficiently. What you will learn Implement and configure Tableau CRM from scratch Build your first Tableau CRM analytics app and embed your Tableau CRM dashboards in Salesforce to enhance user adoption Connect Salesforce and external data with Tableau CRM and create datasets Create a data recipe and get familiar with the recipe UI Build a custom dashboard in Tableau CRM using the dashboard editor Use lenses to create a Tableau CRM analytics dashboard Configure and implement data security and governance Build configured record actions to automate data directly in Salesforce Who this book is for This book is for data analysts, business analysts, BI professionals, and Salesforce users who want to explore Tableau CRM's capabilities and features. Basic knowledge of Sale...